When Actors Take Over the Products: Showcasing Hallyu-Influenced Indonesian Beauty Product Advertising Through Multimodal Analysis - Herman, Herman; Derin, Tatum; Purba, Ridwin; Warman, Jaka Satria; Setiono, Andrew (Lingua Cultura, 2023)
The research attempted to address the research gaps in the semiotics of Korean-related media, considering that there were only a few studies on advertisements that had been influenced by the Korean craze. Capitalizing on the Hallyu Wave, an Indonesian cosmetics company, Scarlett Whitening, changed its Instagram marketing strategy to focus on its South Korean brand ambassador, Song Joong Ki. The data were two Instagram advertisements of Scarlett Whitening that represented their change of strategy in September 2021. The data were analyzed using multimodal analysis to find out the three metafunctions of the advertisements, referring to Kress and Leeuwen’s social semiotics theory. Results show that the representational meaning of both advertisements contains a solid narrative to invite readers to buy the product so that they can be closer to the South Korean actor. The interpersonal metafunction influences consumers to believe that the human model is very familiar with the product, and the compositional metafunction highlights the association between Song Joong Ki’s white skin, white clothes, and white product with the brand’s name. However, the analysis also indicates an extreme spotlight on the South Korean actor and a stark neglect of the product across the linguistic, visual, and spatial semiotic systems. The research is significant in revealing a potentially concerning upcoming business marketing strategy that capitalizes on the popularity of Korean culture at the cost of neglecting the authenticity of their products.